2015
DOI: 10.4018/978-1-4666-6343-5.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology and Learner Autonomy in Language Learning

Abstract: Mobile-Assisted Language Learning (MALL) provides learners with the chance to experience new learning modes that go beyond the classroom context, offering them more flexibility, learning choices in terms of language content, ways of its delivery, learning space, and time, thereby enhancing their learning autonomy. But how are English teachers using MALL? In the attempt to answer this question, a survey is carried out with a sample of 42 English teachers. The results show that the limited use of such devices is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…MALL emerged from Computer-Assisted Language Learning (CALL) and its appropriateness has proved to be of great value for learning (Chinnery, 2006;Kukulska-Hulme, 2009. MALL provides EFL learners with the chance to experience new learning modes that go beyond the classroom context, offering them more flexibility, choices in terms of language content, ways of delivery, learning space, and time, thereby enhancing autonomy (Djoub, 2014;Kukulska-Hulme, 2016).…”
mentioning
confidence: 99%
“…MALL emerged from Computer-Assisted Language Learning (CALL) and its appropriateness has proved to be of great value for learning (Chinnery, 2006;Kukulska-Hulme, 2009. MALL provides EFL learners with the chance to experience new learning modes that go beyond the classroom context, offering them more flexibility, choices in terms of language content, ways of delivery, learning space, and time, thereby enhancing autonomy (Djoub, 2014;Kukulska-Hulme, 2016).…”
mentioning
confidence: 99%
“…Furthermore, Djoub (2016) conducted an empirical study to examine the effect of MALL on students' achievements in language learning and to find out the difficulties learners encounter within this process at the University of Mostaganem, Algeria. She ensured that "Mobile Assisted Language Learning (MALL) provides learners with the chance to experience new learning modes Arab World English Journal www.awej.org ISSN: 2229-9327 88 that go beyond the classroom context, offering them more flexibility, learning choices in terms of context, ways of its delivery, learning space, and time, thereby enhancing their learning autonomy" (p. 294).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…He also confirmed that the results show some improvement in students' productive skills. Furthermore, Djoub (2016) conducted an empirical study to examine the effect of MALL on students' achievements in language learning and to find out the difficulties learners encounter within this process at the University of Mostaganem, Algeria. She ensured that "Mobile Assisted Language Learning (MALL) provides learners with the chance to experience new learning modes Arab World English Journal www.awej.org ISSN: 2229-9327 88 that go beyond the classroom context, offering them more flexibility, learning choices in terms of context, ways of its delivery, learning space, and time, thereby enhancing their learning autonomy" (p. 294).…”
Section: Review Of the Literaturementioning
confidence: 99%